Princeton Seminary (1812-1929) : the leader's lives and works - Steward, Gary. (Phillipsburg, New Jersey : : P & R Publishing, 2014)
Many of the key ideas of the modern era, and Christian responses to them, were formulated at the time of "Old Princeton." Gary Steward introduces us to the great men of Princeton Theological Seminary from its founding to the early twentieth century, together with some of their most important writings. While commemorating the legacy of Old Princeton, this book also places the seminary in its historical and theological contexts--From publisher description.
Includes bibliographical references and index (pages 305-308)
Keywords: Princeton Theological Seminary -- History; Princeton Theological Seminary; Princeton Theological Seminary..; Theological seminary presidents -- Biography; Theological seminary presidents -- Bibliography; Theological seminary presidents -- Portraits; Princeton theology; Princeton theology..; Theological seminary presidents..; Bibliography..; Biography..; History..; Portraits..